2016
DOI: 10.1039/c5nj02470f
|View full text |Cite
|
Sign up to set email alerts
|

Iron(ii) spin crossover complexes with diaminonaphthalene-based Schiff base-like ligands: 1D coordination polymers

Abstract: Iron(ii) spin crossover coordination polymers with diaminonaphthalene derived Schiff base-like ligands were synthesised, and their magnetic and structural properties were analysed. Rigid bridging ligands having up to 40 K wide hysteresis loops were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Please note that the amount of carbon present, as determined by elemental analysis, is too low due to incomplete combustion for all samples. The same difficulties were encountered for similar complexes of this ligand type with extended aromatic units . In addition, SEM images were recorded to analyse the homogeneity of the samples and showed that the samples were homogeneously amorphous (see Figure S1 in the Supporting Information).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Please note that the amount of carbon present, as determined by elemental analysis, is too low due to incomplete combustion for all samples. The same difficulties were encountered for similar complexes of this ligand type with extended aromatic units . In addition, SEM images were recorded to analyse the homogeneity of the samples and showed that the samples were homogeneously amorphous (see Figure S1 in the Supporting Information).…”
Section: Resultssupporting
confidence: 92%
“…A very interesting aspect of this ligand type is that the corresponding iron(II) complexes are SCO active, thus allowing either SCO or CISSS to be observed, depending on the metal centre. Furthermore, the corresponding iron(II) coordination polymers can be functionalised further through the synthesis of polymer/coordination polymer nanocomposite materials…”
Section: Introductionmentioning
confidence: 99%
“…The integrated enthalpy and entropy values are Δ H = 6.78 kJ mol –1 and Δ S = 20.9 J mol –1 K –1 for the HS to LS transition, and Δ H = 6.07 kJ mol –1 and Δ S = 18.3 J mol –1 K –1 for the LS to HS transition, which are consistent with those reported in the literature. 3c , 12c , 14 …”
Section: Resultsmentioning
confidence: 99%
“…Schiff's base reactions are well-known organic reactions that are the main source of several versatile organic moieties and the reaction intermediates responsible for enormous applications in the diversified fields as pharmacy [1], agriculture [2,3], biosciences [4], physical sciences [5], chemical sciences [6], etc. By virtue of its virtual applicability, Schiff bases have attracted great attention in the past few decades [7] and they are very prominent in the research related to organic compounds.…”
Section: Introductionmentioning
confidence: 99%